Silver ion conductivity in AgLa(PO3)4 polyphosphates. (1st April 2022) - Selmi, A.; Ajili, L.; Sdiri, N.; Férid, M.; Horchani-Naifer, K.
Abstract: AgLa(PO3 )4 polycrystalline powder has been prepared by flux method and characterized by X-ray powder diffraction and FTIR spectroscopy. The AgLa(PO3 )4 structure was crystallized in the monoclinic system with space group P21 /n and cell parameters: a = 7.300(5)A°, b = 13.211(9)A°, c = 10.079(7)Å, β = 90.47(4)°, V = 971.99 Å 3 and Z = 4. Ionic conductivities of the AgLa(PO3 )4 powder were carried out by impedance spectroscopy measurements over a temperature range from 300 °C to 650 °C. A simple equivalent circuit model is described and electrical characteristics predicted by the model are compared with those obtained experimentally. The conductivity values obtained from this sample were 1.8 × 10 −7 and 6 × 10 −6 [S.cm −1 ] at 350 and 650 °C, respectively. The activation energy in the temperature range investigated is Ea = 0.65 eV corresponds to the mobility of Ag + cations situated in the tunnels cavities. The most probably Ag + ion transport between defect states may take place by a quantum tunnelling and hopping processes. The conduction and relaxation processes in the studied AgLa(PO3 )4 polycrystalline powder are temperature dependent. Highlights: Polyphosphates containing silver and rare-earth cations show promising conduction properties. The investigated AgLa(PO3 )4 demonstrated low activation energy and better conductivity than similar compared materials. The AgLa(PO3 )4 powder showed a no Debye relaxation type. Conduction pathways are based on either; quantum tunneling and hopping process of Ag + ion between defect states.